2022
DOI: 10.3389/fnagi.2022.959394
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain functional connectivity of hippocampus in mild cognitive impairment

Abstract: Mild cognitive impairment (MCI) is the prodromal stage of Alzheimer’s Disease (AD). Prior research shows that females are more impacted by MCI than males. On average females have a greater incidence rate of any dementia and current evidence suggests that they suffer greater cognitive deterioration than males in the same disease stage. Recent research has linked these sex differences to neuroimaging markers of brain pathology, such as hippocampal volumes. Specifically, the rate of hippocampal atrophy affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The development of Alzheimer's disease [69,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer's disease have been investigated . Numerous studies are also available regarding treatments with probiotics [139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%
“…The development of Alzheimer's disease [69,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer's disease have been investigated . Numerous studies are also available regarding treatments with probiotics [139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its size, the pig brain also offers the possibility to isolate large amounts of mitochondria that ensures stability of respiratory parameters when isolating from distinct brain regions (Fišar and Hroudová, 2016), which may enhance the predictive value of this preclinical model (Perleberg et al, 2018). Additionally, this study focused on females, which have greater cognitive deterioration compared to males at the same stage of neurodegenerative disease (Cerri et al, 2019;Williamson et al, 2022). However, several limitations must be considered when interpreting the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated that women have a higher prevalence of AD, with two-thirds of AD cases residing in women [241,242]. While the prevailing view attributes this discrepancy to women's longer average lifespan (4.5 years more than men) [243], other factors contribute.…”
Section: Sex Differences In Ad and Cerebral Vascular Functionmentioning
confidence: 99%
“…While the prevailing view attributes this discrepancy to women's longer average lifespan (4.5 years more than men) [243], other factors contribute. These include: 1) women born in the 20 th century had lower education levels and incomes than men which contributes to an increasing number of dementia cases [243]; 2) men have a higher cardiovascular death rate in middle age, resulting in a lower rate of dementia in those that survive to an advanced age [243]; 3) women lose the neuro- [244] and vascular-protective [245] effects of sex hormones after menopause; 4) women's brains are more vulnerable to the effects of AD pathology and a weaker interhemispheric functional connectivity compared to men [241,242]. Despite the notable sex differences in the incidence of AD among humans (>3000 studies in 5 years), there has been a shortage of studies to determine the mechanisms involved.…”
Section: Sex Differences In Ad and Cerebral Vascular Functionmentioning
confidence: 99%